Reform of Social Work Internship under the Context of the New Setting of Society Work Department - Long, Ling; Chen, Shihai (Journal of Educational Research and Policies, 2025)
The society work department provides new opportunities and injects fresh developmental momentum into the development of social work in China. Its core functions, such as coordinating social governance and advancing people's livelihood services, pose new requirements for social work professional education, particularly for the social work internship. While, the social work internship had a disconnect between internship content and governance needs, imperfect collaborative mechanisms, and a singular evaluation system. Based on the functional orientation of the society work department, the study explores pathways for social work internship reform from five aspects such as internship content, collaborative mechanisms, evaluation methods, professional cognition, and safeguards, aiming to cultivate high-quality social work talents that meet the needs of national governance.